Mode of interaction of the G?o subunit of heterotrimeric G proteins with the GoLoco1 motif of Drosophila Pins is determined by guanine nucleotides. - Lüchtenborg, A.M.; Purvanov, V.; Melnik, B.S.; Becker, S.; Katanaev, V.L. (Bioscience Reports, 2015)
Drosophila GoLoco motif-containing protein Pins is unusual in its highly efficient interaction with both GDP- and the GTP-loaded forms of the ?-subunit of the heterotrimeric Go protein. We analysed the interactions of G?o in its two nucleotide forms with GoLoco1-the first of the three GoLoco domains of Pins-and the possible structures of the resulting complexes, through combination of conventional fluorescence and FRET measurements as well as through molecular modelling. Our data suggest that the orientation of the GoLoco1 motif on G?o significantly differs between the two nucleotide states of the latter. In other words, a rotation of the GoLoco1 peptide in respect with G?o must accompany the nucleotide exchange in G?o. The sterical hindrance requiring such a rotation probably contributes to the guanine nucleotide exchange inhibitor activity of GoLoco1 and Pins as a whole. Our data have important implications for the mechanisms of Pins regulation in the process of asymmetric cell divisions.